Ukuran Perusahaan Memoderasi Pengaruh Leverage Pada Tax Avoidance - Indira, Irma; Nisa, Latifatun; Dedyansyah, Achmad Farid; Salukh, Agustinus; Putro, Guruh Marhaenis Handoko (Politeknik Raflesia Press, 2024)
Tax is the largest source of revenue for the state which is used to finance state development, build infrastructure, finance government, finance health and education facilities and is used for the welfare of its people. This study aims to determine the effect of Leverage on Tax Avoidance with firm size as a moderating variable. The samples obtained were 75 sample data from 25 goods and consumption companies during 2019-2022 which were selected using the purposive sampling method. Data analysis techniques used descriptive statistical tests, classic assumption tests (normality test, multicollinearity test, autocorrelation test, heteroscedasticity test), multiple linear regression tests, Moderated Regression Analysis (MRA) test, and hypothesis testing (t test, Coefficient of determination test) with SPSS application program version 25.The results of this study indicate that, Leverage has an effect on Tax avoidance, company size has an effect on tax avoidance and the results show that company size is able to moderate leverage.